Supervision Function at the SETDAPROVSU Governor's Office on the Management of Grants for the Construction of Houses of Worship in North Sumatra - Syopiah Syopiah; Muhammad Arif (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The Governor of North Sumatra is the highest position in the province of North Sumatra. The Governor of North Sumatra is the official responsible for leadership in North Sumatra, proposing and enacting regional laws, and representing the Province of North Sumatra in and out of court together with the deputy governor and 100 members of the North Sumatra Regional House of Representatives. The Governor and Deputy Governor of North Sumatra are elected through general elections which are held every 5 years. The current governor of North Sumatra is Edi Rahmayadi.